The Relationship among Communication, Leadership Behaviour and Performance - Semarco, Stanley K. M. (Journal of Communications, Media & Society, 2009)
The present study explored the relationship among communication, leadership behaviours and performance. It was hypothesised that leader's communication would predict the leader’s exhibition of leadership behaviours and performance. Participants (104 students) were asked to provide communication, leadership behaviour and performance ratings of lecturers within classroom instructional setting. Results indicated that communication was a better predictor of performance and choice of leadership behaviours. The current study provides support in demonstrating the validity and practicability of using communication dimensions as a predictive variable of leadership success. The findings were discussed.
Research Article
Keywords: Communication, Leadership, Behaviour, Leadership Behaviours